2014
DOI: 10.1111/ppa.12264
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of brown rot fungi on blossoms and fruit in stone fruit orchards in Greece

Abstract: Brown rot is a devastating disease of stone fruits caused by Monilinia spp. This study was conducted to investigate the disease aetiology on blossoms and fruit in peach, apricot, sweet cherry and plum orchards, in Greece. In total, 1433 isolates obtained from orchards located in the main stone fruit production regions of Greece were identified to species based on the presence/size of a cyt b intron. Monilinia laxa and M. fructicola were detected at frequencies of 59 and 41%, respectively, while M. fructigena w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
8
27
0
1
Order By: Relevance
“…However, no conidial germination was recorded by these authors when RH was lower than 87%. Our results are in agreement with those of Papavasileiou et al (2015) who found that maximum germination of M. laxa and M. fructicola conidia occurred when the isolates were grown on PDA and the temperature was Fig. 1.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…However, no conidial germination was recorded by these authors when RH was lower than 87%. Our results are in agreement with those of Papavasileiou et al (2015) who found that maximum germination of M. laxa and M. fructicola conidia occurred when the isolates were grown on PDA and the temperature was Fig. 1.…”
Section: Discussionsupporting
confidence: 83%
“…These results were similar to those of Papavasileiou et al (2015) who reported that the conidia of five M. laxa isolates and five M. fructicola isolates did not germinate on PDA at 35°C. However, Casals et al (2010) reported that the germination of conidia of three different Monilinia isolates, one M. laxa isolate, one M. fructigena isolate, and one M. fructicola isolate, occurred at 35°C, but not at 38°C.…”
Section: Tablesupporting
confidence: 81%
See 3 more Smart Citations